VIRTUAL MACHINING AND FINITE ELEMENT ANALYSIS OF SPIRAL BEVEL GEAR - WANG ZhongHou; HUANG CongYang; SHI ZhaoYao; LIU HeTao; QIAN XiaoQi; AIZOH Kubo (Jixie qiangdu)
According to the structure characteristics and motion principle of traditional machine tools,the spiral bevel gear is virtual machined by Catia. By comparing the machining accuracy with the theoretical model,the rationality and accuracy of the modeling are proved. Hypermesh is used to mesh the gears,which is imported into ABAQUS for finite element analysis to extract the curve of transmission error and contact wire with the increase of load,the amplitude of transmission error fluctuation decreases,but the amplitude of deviation from zero line increases. It shows that the transmission of spiral bevel gear is more stable and the transmission accuracy decreases with the increase of load,which is consistent with the dynamic characteristics of spiral bevel gear,indicating that the performance of virtual machining gear is good. When the contact performance and transmission error curve of the gear formed by virtual machining are not ideal in the finite element analysis,according to the principle of modification, the machining parameters can be adjusted and gear is reprocessed in Catia. The contact and transmission performance of the reconstructed gear can be improved in the analysis. In Catia simulation machining,the error can be added artificially to provide a model for the finite element analysis of the gear with error,which is convenient for people to study the dynamic characteristics of the gear with error. In the gear design stage,the finite element method is used to study the contact performance and transmission characteristics of the gear,so as to predict and evaluate the quality of the virtual machining gear,analyze the relationship between the gear performance and the adjustment parameters of the machine tool,and play an important role in the reverse adjustment of the processing adjustment parameters of the spiral bevel gear.